Particle emissions of Euro VI, EEV and retrofitted EEV city buses in real traffic. (July 2019) - Järvinen, Anssi; Timonen, Hilkka; Karjalainen, Panu; Bloss, Matthew; Simonen, Pauli; Saarikoski, Sanna; Kuuluvainen, Heino; Kalliokoski, Joni; Dal Maso, Miikka; Niemi, Jarkko V.; Keskinen, Jorma; Rönkkö, Topi
Abstract: Exhaust emissions from traffic significantly affect urban air quality. In this study, in-traffic emissions of diesel-fueled city buses meeting enhanced environmentally friendly vehicle (EEV) and Euro VI emission limits and the effects of retrofitting of EEV buses were studied on-road by chasing the buses with a mobile laboratory in the Helsinki region, Finland. The average emission factors of particle number (PN), particle mass (PM1 ) and black carbon mass (BC) were 0.86·10 15 1/kgfuel, 0.20 g/kgfuel and 0.10 g/kgfuel, respectively, for EEV buses. For Euro VI buses, the emissions were below 0.5·10 15 1/kgfuel (PN), 0.07 g/kgfuel (PM1 ) and 0.02 g/kgfuel (BC), and the exhaust plume concentrations of these pollutants were close to the background concentrations. The emission factors of PM1 and BC of retrofitted EEV buses were at the level of Euro VI buses, but their particle number emissions varied significantly. On average, the EEV buses were observed to emit the largest amounts of nanocluster aerosol (NCA) (i.e., the particles with size between 1.3 and 3 nm). High NCA emissions were linked with high PN emissions. In general, results demonstrate that advanced exhaust aftertreatment systems reduce emissions of larger soot particles but not small nucleation mode particles in all cases. Graphical abstract: Image 1 Highlights: Particle emissions from Euro VI buses are low in real traffic. Retrofitting of aftertreatment system effectively reduces particle emission . Sub 3 nm particles have been detected in the bus exhaust plumes. Number emissions of sub 3 nm particles are linked with number of larger particles. Abstract : Emission control technologies used in Euro VI buses are effectively reducing soot and NOx emissions in real operation, but small sub-3 nm particles exist in variable concentrations in the exhaust of Euro VI, EEV and retrofitted EEV buses.